Analisis Peluang Kewirausahaan Lembaga Dakwah - Hasibuan, Ilham; Castrawijaya , Cecep (Institut Agama Islam Negeri Parepare, 2024)
This research discusses entrepreneurial opportunities for da'wah institutions to support financial independence and strengthen their social role in the community. Dakwah institutions have the potential to run businesses that are not only profit-oriented but also support the mission of dakwah and Islamic values. Using SWOT analysis, this research evaluates the strengths, weaknesses, opportunities, and threats faced by da'wah institutions in developing sharia-based businesses. The results show that entrepreneurship can be a solution for da'wah institutions to achieve financial sustainability while also having a positive impact on the community. Keywords: Da'wah institutions, entrepreneurship, SWOT analysis, financial independence.